TURKISH AND LITERATURE TEXTBOOKS LANGUAGE AND CULTURE TRANSMITTING AN INVESTIGATION OF THE ROLE AND IMPORTANCE - Mesut BULUT (Fırat University, 2019)
All ages of human life as a social being built on certain values, a fact that can not be denied. Cultural values of communities is at the beginning of the values that form the basis. Textbooks, transmitting cultural values of the societies play an important role as a part of educational activities. Teach students the cultural values, adopting and transferring these values to future generations of students to acquire the habit of reading pleasure and, training and personality shaping the texts that make up the textbook content, type, theme, to be distinguished in terms of issues such as the selection is very important. Regulate social life, especially in our age, blunted face keeps away from these values, we observe an increasingly organizing human life. Position of the identity of transfer of cultural values of our nation for future generations, and in this context, the Turkish as the transmitter of the most important of these values more accurately and ensure the appropriate use of the essence, Turkish and literature are among the objectives of education. Achieving these goals, the most utilized resource for students and teachers capable of textbooks is of great importance. In particular the choice of course text books and carrying these values accurately reflect the substance of the texts and the suitability of our nation should not be ignored. Because these values in students the best offer of all kinds of mother tongue and making use of the wealth created by the presence of these literary works are won through the national and universal values. In this study, Turkish and literature textbooks used in teaching evaluations are made on the importance of cultural values and transfer its action of these various suggestions were made.